Analisis Kinerja Protokol Routing pada Arsitektur Delay Tolerant Network Terhadap Beberapa Pola Pergerakan - Hafidz Rizal; Widhi Yahya; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Delay Tolerant Network (DTN) is a network does not matter for delay, disruption, and disconnection from the internet. The continuous movement for send a massege will produce movement patterns, like patterns of random, scheduled, and patterned movements. This research to know performance of routing protocol of Prophet, Maxprop, Epidemic, and Spray And Wait with addition of node and speed on random, scheduled and patterned movement. The One is used for simulation and OpenJUMP for the make a map. The results form the addition of node and speed is probability delivery and overhead rasio has increased and average latency is decreased. The protocol routing maxprop has better performance in the pattern of random movement and patterned movement, because on the addition of nodes and speed produce the value on delivery probability is 63% and 55% in random movement, 62% and 59% patterned movement, average latency is 33% and 31% in random movement, 32% and 32% patterned movement, and overhead ratio is 83% and 78% in random movement, 83% and 88% patterned movement. Then the pattern of scheduled movements protocol routing spray and wait has better performance, because on the addition of nodes and speed produce the value on average latency is 37% and 44%, overhead ratio is 4% and 8%, and delivery probability is 41% and 40%.